Enhancing Career Adaptability Among University Students: An Intervention Study - Wetstone, Hannah; Rice, Kenneth G. (Journal of career development, 2023)
Recent college graduates are navigating a complex labor market due to the COVID-19 pandemic, changing economic conditions, and advancing technologies. Career adaptability, a psychosocial construct focused on managing career transitions, is critical for college students in this environment. Career adaptability interventions have shown promising results, but many are time consuming or involve one-on-one counseling, and none have focused on US college samples, which prompted this study. We tested a brief career adaptability training on a sample of 89 US college students and measured its effect on participants’ career adaptability resources (career concern, career control, career curiosity, career confidence) and career adapting responses (career decision self-efficacy, career planning). Results showed no increase in career adaptability resources or career planning but indicated an increase in career decision self-efficacy, suggesting that brief interventions may be effective for some desired outcomes but not others. Future research should examine which intervention ingredients are necessary to enhance career adaptability.